2022
DOI: 10.1109/access.2022.3217794
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Blockchain in Business Processes: A Comprehensive Review

Abstract: Blockchain (BC), as an emerging technology, is revolutionizing Business Process Management (BPM) in multiple ways. The main adoption is to serve as a trusted infrastructure to guarantee the trust of collaborations among multiple partners in trustless environments. Especially, BC enables trust of information by using Distributed Ledger Technology (DLT). With the power of smart contracts, BC enforces the obligations of counterparties that transact in a business process (BP) by programming the contracts as transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…From Table 2, it is observed that the time taken to create a block and validate the transactions is nearly 0.02 ms, while the computation time is approximately 0.03 ms as proposed by the authors in Ref. 6 for a block that can accommodate nearly 600 bits, while in Ref. 16 the time taken to create a single block for nearly 500 bits as maximum block size is as high as 0.9 ms, while the time to validate is nearly 0.7 ms.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…From Table 2, it is observed that the time taken to create a block and validate the transactions is nearly 0.02 ms, while the computation time is approximately 0.03 ms as proposed by the authors in Ref. 6 for a block that can accommodate nearly 600 bits, while in Ref. 16 the time taken to create a single block for nearly 500 bits as maximum block size is as high as 0.9 ms, while the time to validate is nearly 0.7 ms.…”
Section: Resultsmentioning
confidence: 93%
“…Another difficult issue that requires consideration in the present world is the choice of a platform to handle the logical control of IoT devices. 6 Through the integration of programming methodologies, several metrics, either cost-or distance-based, can be used to find anomalies in the devices. 7 In the current environment, adopting the newest technology trends is difficult, especially with the massive amount of data that is flooding the internet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jabbar et al [ 4 ] have discussed about the various issues and challenges in implementing blockchain-enabled supply chain using different case studies and concluded that many organizations have taken steps to build a blockchain-enabled platform for efficient business.…”
Section: Literature Surveymentioning
confidence: 99%
“…Dasaklis et al [ 4 ], have done an extensive survey in understanding the implementation of blockchain-enabled supply chains and explored the various features and challenges through research works. The use of blockchains in the production process promises to be an appealing research topic for future studies, especially in the age of cybersecurity.…”
Section: Introductionmentioning
confidence: 99%